Islamic Divorce in the Twenty-First Century : A Global Perspective. - Stiles, Erin E.; Yakin, Ayang Utriza; Giunchi, Elisa; Bernard-Maugiron, Nathalie; Essop, Fatima; Issaka-Toure, Fulera; Landry, Jean-Michel.; Schulz, Dorothea; Diallo, Souleymane; Steenberg, Rune. (New Brunswick : Rutgers University Press, 2022)
Islamic Divorce in the 21st Century shows the wide range of Muslim experiences in marital disputes and in seeking Islamic divorces. For Muslims, having the ability to divorce in accordance with Islamic law is of paramount importance. However, Muslim experiences of divorce practice differ tremendously. The chapters in this volume discuss Islamic divorce from West Africa to Southeast Asia, and each story explores aspects of the everyday realities of disputing and divorcing Muslim couples face in the twenty-first century. The book's cross-cultural and comparative look at Islamic divorce indicates that Muslim divorces are impacted by global religious discourses on Islamic authority, authenticity, and gender; by global patterns of and approaches to secularity; and by global economic inequalities and attendant patterns of urbanization and migration. Studying divorce as a mode of Islamic law in practice shows us that the Islamic legal tradition is flexible, malleable, and context-dependent.
Frontmatter -- Contents -- Series Foreword -- Preface and Acknowledgments -- List of Abbreviations -- Note on Transliteration -- Introduction: Muslim Marital Disputes and Islamic Divorce Law in Twenty-First- Century Practice -- Part One. State Politics and Divorce Law: Reform and Recommendations -- 1. Divorce by khulʻ in Pakistani Courts: Expanding Women's Rights through Reconfiguring Religious Authority -- 2. Male-Initiated Divorce before the Egyptian Judiciary -- 3. Problems of and Possibilities for Islamic Divorce in South Africa -- Part Two. Gendered Strategies and Judicial Responses in Marital Disputing -- 4. Women in the Search of Sexual Pleasure: Divorce on Grounds of Sexual Dissatisfaction in Indonesian Religious Courts -- 5. "I Divorced Him but He Said He Has Not Divorced Me": Gendered Perspectives on Muslim Divorce in Accra, Ghana -- 6. Undoing Marriage in Lebanon: Divorce within and beyond Family Courts -- Part Three. Islamic Divorce in the Context of Global Patterns of Mobility, Upheaval, and Changing Household Economies -- 7. Islamic Renewal, Muslim Divorce, and Gender Relations in Mali -- 8. A "Much-Married Woman" Revisited: Kinship Perspectives on the High Frequency of Divorce among Uyghurs in Southern Xinjiang, China -- 9. The Ends of Divorce: Marital Dispute as a Locus of Social Change in India -- Conclusion: Islamic Divorce in Context and in Action: Notes from the Field -- Notes on Contributors -- Index
Description based upon print version of record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Marriage -- Religious aspects -- Islam; Divorce -- Religious aspects -- Islam; Husband and wife (Islamic law); Separation (Islamic law); Divorce (Islamic law); Divorce -- Aspect religieux -- Islam; Époux (Droit islamique); Séparation de corps (Droit islamique); Divorce (Droit islamique); RELIGION / General; Divorce (Islamic law); Divorce -- Religious aspects -- Islam; Husband and wife (Islamic law); Marriage -- Religious aspects -- Islam; Separation (Islamic law); Islamic divorce, Islamic family dynamics, divorce law, Islamic law, law interpretation, Islamic marriage, South Asian law, world law, law in the Islamic states, Southeast Asian law, Muslim struggle, Muslim law, Muslim divorces, divorce practice, Islamic legal tradition, Marital disputes, Pakistani court, Pakistani courts, Egyptian judiciary system, Egyptian courts, South African courts, Egyptian law, Pakistani law, South African law